A creative partnership the actor and director (North Ryde, NSW. : Australian Film Television & Radio School, 1982)
The program traces a segment of a feature film from casting to the shoot and focuses on the development of the actor/director relationship through the various stages of production
Keywords: Motion pictures -- Production and direction; Motion pictures -- Casting